1992
DOI: 10.1051/rnd:19920108
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal mucosal morphometry and ileal epithelial renewal in conventional and germ-free rats fed an amylomaize starch diet

Abstract: Summary ― Intestinal mucosal morphometry and ileal epithelial renewal were studied in conventional (CV) and germ-free (GF) rats fed either poorly digestible amylomaize or normal maize starch diets. Intestinal morphometry and position of labelled enterocytes were studied at various times after tritiated thymidine injection. With amylomaize starch diet, no difference was observed in the size of crypts (C), villi (V) and C + V between duodenum and jejunum both in CV and GF rats. In the ileum, however, valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Conversely, Shurson et al (15) reported that germ-free pigs had longer ileal and duodenal villi but shorter jejunal villi compared with their conventional counterparts. In the germfree chicken (21) and rodent (17,22,23) villus length was reported to decrease progressively along the SI from the duodenum to the distal ileum. Interestingly, Ishikawa et a1.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Shurson et al (15) reported that germ-free pigs had longer ileal and duodenal villi but shorter jejunal villi compared with their conventional counterparts. In the germfree chicken (21) and rodent (17,22,23) villus length was reported to decrease progressively along the SI from the duodenum to the distal ileum. Interestingly, Ishikawa et a1.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Shurson et al (1990) reported that germ-free pigs had longer ileal and duodenal villi but shorter jejunal villi compared to their conventional counterparts. In the germ-free chicken (Rolls et al, 1978) and rodents (Komai and Kimura, 1979;Ishikawa et al, 1986;Meslin et al, 1992) villus length was reported to decrease progressively along the small intestine from the duodenum to the distal ileum. This regional response was suggested to be the result of regional variation in microbial species diversity and abundance.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the hydroxyl group in position 12 prevents the inclusion of this bile acid in BCD, dramatically reducing BCD affinity for cholic and deoxycholic acids (34). Moreover, we have previously demonstrated that poorly digestible carbohydrates, such as lactose or amylomaize starch (the BCD precursor), increased the size of ileal villi and stimulated the ileal absorption of taurocholate in rats (39)(40)(41)(42). Thus, our data suggest that BCD reduces the reabsorption of chenodeoxycholic acid and enhances that of cholic acid.…”
Section: Effects Of Bcdmentioning
confidence: 99%